2014
DOI: 10.1039/c4sm00704b
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles as tracers of the gelation dynamics of a natural biopolymer physical gel

Abstract: The gelation of methylcellulose in water has been studied by X-ray photon correlation spectroscopy, electrophoresis and rheological measurements by looking into the dynamics of silica nanoparticles as tracers in the polymer matrix. The temperature and scattering vector dependence of the structural relaxation time is investigated at the nanometric length scale during the formation of the strong gel state. We find a stress-dominated dynamics on approaching the gel state, characterized by a hyper-diffusive motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
4
31
1
Order By: Relevance
“…These data are in agreement with the first results obtained for methylcellulose A4M adsorbed on the same silica particles [26]. It is demonstrated that the interaction is very great for the smaller amounts of added methylcellulose (lower than 5 mg/L).…”
Section: Adsorption Isothermsupporting
confidence: 82%
See 2 more Smart Citations
“…These data are in agreement with the first results obtained for methylcellulose A4M adsorbed on the same silica particles [26]. It is demonstrated that the interaction is very great for the smaller amounts of added methylcellulose (lower than 5 mg/L).…”
Section: Adsorption Isothermsupporting
confidence: 82%
“…Different methods have been proposed to study the adsorption of a polymer at a solid interface [25][26][27][28][29][30][31]. The technique has to be chosen in dependence of the system studied (the nature of the neutral or charged polymer, the bulk concentration of the polymer, the external salt concentration).…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation
“…an exponent β < 1 is found, this behaviour is referred to as "stretched behaviour". On the contrary in the last decade an unusual behaviour characterized by a β exponent β > 1 has been observed and referred to as "compressed behaviour" [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. These two peculiar trends correspond to different microscopic dynamics of the particles.…”
Section: Introductionmentioning
confidence: 92%
“…Both stretched and compressed behaviours of the intensity autocorrelation functions are found and discussed in relation to previous studies and on the light of the presence of attractive and repulsive micro- scopic interactions versus the application of external stresses. The different dynamical behaviours observed here in a single system are general features individually observed in several systems as molecular liquids [28,29], colloidal hard spheres [30], colloids [2,10], clays [3,4,5,13,15], metallic glasses [11], polymers [6,7,9,14], supercooled liquids [8].…”
Section: Introductionmentioning
confidence: 93%